2018
DOI: 10.4103/jomfp.jomfp_188_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mucin-1 in oral squamous cell carcinoma and normal oral mucosa: An immunohistochemical study

Abstract: Background:Mucins are high-molecular-weight glycoproteins with a high O-linked carbohydrate content, which are synthesized by many secretory epithelial cells as membrane-bound and/or secreted products. Mucin-1 (MUC1) is a transmembrane mucin that protects and lubricates the mucous membranes of the human body and involves itself in various cellular functions such as growth, differentiation and signaling. An aberrant expression of MUC1 has been demonstrated in various human cancers. Many studies on MUC1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The strong association between MUC1 expression level in OPMDs in comparison with OSCC group may be possibly explained by involvement of other factors in the progression of the highly complex oral malignancy after the initial stage. The latter results are consistent with the results reported by other studies (Nitta et al, 2000;Thakur et al, 2018;Utispan & Koontongkaew, 2021) which reported no statistically significant difference of MUC1 expression between the different clinical stages of OSCC. However, positive associations between expression of MUC1/DF3 and clinicopathologic characteristics (tumor aggressiveness) were found in the study by Hamada et al (Hamada et al, 2012).…”
Section: Ta B L Esupporting
confidence: 93%
“…The strong association between MUC1 expression level in OPMDs in comparison with OSCC group may be possibly explained by involvement of other factors in the progression of the highly complex oral malignancy after the initial stage. The latter results are consistent with the results reported by other studies (Nitta et al, 2000;Thakur et al, 2018;Utispan & Koontongkaew, 2021) which reported no statistically significant difference of MUC1 expression between the different clinical stages of OSCC. However, positive associations between expression of MUC1/DF3 and clinicopathologic characteristics (tumor aggressiveness) were found in the study by Hamada et al (Hamada et al, 2012).…”
Section: Ta B L Esupporting
confidence: 93%
“…The expression of MUC1 in the buccal area and salivary glands has been described before. 57 - 59 MUC3 has shown to be upregulated in mucosal tissue (intestine) in a stress response, 60 but no data about expression in the oral mucosa has been described yet. MUC15 was shown to be expressed in explants of human oral mucosal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, mucin-conforiong amino acid threonine is affecting the metaststic activity and it might be reasonable to attribute the presence of the NAA-like peak observed on MRS in our two melanoma patients to this particular mucin component. Furthermore, a recent immunohistochemical study con rmed the presence of mucin-1 (MUC-1) in around 70% of oral squamous cell carcinomas [14].…”
Section: Discussionmentioning
confidence: 99%